2015
DOI: 10.1186/s12891-015-0714-z
|View full text |Cite
|
Sign up to set email alerts
|

A dose response analysis of a specific bone marrow concentrate treatment protocol for knee osteoarthritis

Abstract: BackgroundPrior studies describing the treatment of symptomatic knee osteoarthritis with injections of bone marrow concentrate have provided encouraging results. The relationship between the cellular dose contained within the bone marrow concentrate and efficacy of the treatment, however, is unclear. In the present study we describe clinical outcomes for symptomatic knee osteoarthritis in relation to higher and lower cell concentrations contained within a bone marrow concentrate treatment protocol.MethodsData … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 44 publications
6
71
2
1
Order By: Relevance
“…The cellular doses administered in the present study were adequately high at all 3 occasions in both groups that received stem cells. Dose response analyses have failed to assign better outcomes with higher doses [3], and in this sense, repeated MSC cultures to ensure higher cell doses seem to be an unjustified risk at a great cost [31]. When autologous PB or BM is the source of the cellular therapy, synergistic action of all cellular components and their compatible and synchronous secretome seems to confer all the necessary endogenous advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular doses administered in the present study were adequately high at all 3 occasions in both groups that received stem cells. Dose response analyses have failed to assign better outcomes with higher doses [3], and in this sense, repeated MSC cultures to ensure higher cell doses seem to be an unjustified risk at a great cost [31]. When autologous PB or BM is the source of the cellular therapy, synergistic action of all cellular components and their compatible and synchronous secretome seems to confer all the necessary endogenous advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma or osteoarthritis (OA) creates fullthickness chondral defects that cannot efficiently heal, thus leading to significant long-term disability [1]. Conventional treatments are unable to reverse or halt OA progression and are thus often restricted to activity modification, weight loss, and the management of symptoms (pain and inflammation) that, depending on disease severity, range from conservative treatment to surgical intervention, including total knee arthroplasty (TKA), with the numbers and costs of the latter having doubled between 2001 and 2012 [3]. Projections for 2030 estimate a 7-fold increase in TKA, while 67 million Americans will be afflicted by OA [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saw and colleagues use the same number and timing of injections in their treatment protocol. Also, dose response studies have found that patients with osteoarthritis who received an IA injection with a higher concentration of MSCs experienced better clinical and histological results than patients who received a lower concentration of cells [30] [31].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Some authors argue that the therapeutic potential of BMC is due to its constitutive mononuclear cell population that enables the tissue regeneration through the secretion of growth factors that would modulate the heterogeneous population in the niche. 22,23 Nevertheless, a full knowledge of the role of BMC for OA treatment is still scarce due to the complexity of this biological system.…”
Section: Introductionmentioning
confidence: 99%